Examples of terracotta models of Nile boats from the Ptolemaic and Roman periods. Symbolism and significance - Jędraszek , Sławomir (Acta Archaeologica Lodziensia, 2023)
The subject of this article is terracottas depicting boats, whose original designs could have been utilized for navigation on the Nile. Like other terracotta artefacts they are prone to various interpretations, including religious, cultic, symbolic, and even more prosaic interpretations. The primary hypothesis presented in this text suggests that their symbolic significance is associated with the household cult of individuals particularly connected with navigating the waters of the Nile.